A német egyesületi modell és kialakulása - Papházi, Tibor (Szociológiai Szemle, 2024)
The formation of modern associations accompanied the disintegration of the society of estates. There arose social groups which sought to achieve their political goals by uniting in associations. Another impulse to form associations was provided by „social problems” demanding the union of forces in coping with the social inequalities created by developing capitalism. The groups which created associations belonged, in respect of their property relations, culture, and political aspirations, to the middle class. Their opposition to feudal society is also evident in the organization of their associations, which reflected the ideas of civil constitutional thought. For instance, the functions of decision and execution came to be separated into different roles; denying privileges of birth, members had equal rights; positions were no more hereditary but gained through election. In its organization an association may go through changes. The main form these changes take is a shift from a small and amorphous organization to a large, bureaucratized, vertically and horizontally differentiated association. Association may also change into another type of organization: for instance, a political party.